Pornography exposure among adolescents: awareness, attitudes and knowledge of Malay Muslim mothers - Norazman, Anisa Haida; Uzir, Bisha Fathamah; Zaini, Syahrir; Rostam, Muhamad Ashraf; Abdul Hamid, Siti Hazariah (IIUM Press, 2025)
Background: Adolescent exposure to online pornography has become a growing public health concern with implications for their psychological and sexual development. This study explores how Malay Muslim mothers perceive and manage their children’s exposure to sexually explicit online content, focusing on parental awareness, preventive strategies, and influencing socio-educational factors. Methods: A qualitative descriptive design was employed, involving semi-structured interviews with sixteen mothers of children aged 3–17 years. Data were analyzed using reflexive thematic analysis guided by Parental Mediation Theory to understand how parental education, digital literacy, and cultural beliefs shape monitoring and communication practices. Results: Three main themes emerged: Parental Challenges and Strategies in Regulating Gadget Use; Addressing Pornography Exposure in Children; and Sex Education and Communication at Home. Results revealed that while parents are aware of the risks, most rely on schools for formal sex education and face barriers in discussing sensitive topics. Parents with higher educational levels reported stricter digital control, while those from lower-income backgrounds often lacked digital literacy or resources to use monitoring tools. Conclusion: The study highlights how parental education, digital literacy, and cultural values influence Malay Muslim mothers’ mediation of their children’s online experiences. Strengthening parental confidence and providing accessible resources for low-income families may enhance preventive education and communication regarding online sexual exposure